Preparation method of NH2-UIO-66 modified meta-aramid lithium ion battery diaphragm

By adopting non-solvent-induction separation method in lithium ion battery diaphragm, a total of PMIA and NH2-UIO-66 are mixed to form a composite diaphragm, which solves the problem of the existing diaphragm heat stability and insufficient li+migration rate. Electrochemical performance and safety.

CN119369600APending Publication Date: 2025-01-28HEBEI UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411517912.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-18
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The thermal stability and Li+ mobility of existing lithium-ion battery separators are low, resulting in safety problems and poor electrochemical performance.

Method used

The non-solvents induced separation method, and the NH2-UIO-66 nanometer particles are prepared through the water heat synthesis method, and they are mixed with PMIA to form PMIA/NH2-UIO-66 composite diaphragm to improve the heat stability of the diaphragm and ion transport performance.

Benefits of technology

Improve the thermal stability and electrochemical properties of lithium -ion batteries, inhibit the growth of lithium branches, enhance the mechanical strength, and ensure the safety and long life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369600A_ABST
    Figure CN119369600A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an NH2-UIO-66 modified meta-position aramid fiber lithium ion battery diaphragm. The preparation method of the composite porous membrane comprises the following steps: firstly, preparing NH2-UIO-66 nanoparticles by a simple hydrothermal synthesis method, then blending the NH2-UIO-66 nanoparticles with a PMIA slurry, and preparing the spongy uniform porous PMIA / NH2-UIO-66 composite membrane by taking meta-aramid PMIA as a support skeleton of a thermal stability material and NH2-UIO-66 as a filler and by a non-solvent phase inversion method. The diaphragm obtained by the invention has thermal stability and lithium dendrite growth inhibition performance, and when the composite porous membrane is used as the lithium ion battery diaphragm, the thermal stability and electrochemical performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion battery diaphragm material, belonging to the technical field of polymer material preparation; the invention also relates to a study of the electrochemical performance of the battery by the diaphragm material in a lithium ion battery, belonging to the technical field of electrochemical detection. Background Art

[0002] High energy density lithium-ion batteries (LIBs) are widely used in rechargeable electronic devices, new energy vehicles and other fields due to their advantages such as low cost, high safety, no memory effect, low self-discharge, and high number of charge / discharge cycles. The separator is an important component of lithium batteries. It can isolate the positive and negative electrodes to prevent battery short circuits and ensure the transmission of lithium ions. Its performance directly affects the capacity, rate, life, electrochemical performance and safety of the battery. At present, the main lithium battery separators used are polyolefin separators. The low thermal stability and low Li + Mobility is currently the main bottleneck restricting its practical application. Low thermal stability can cause short circuits in the diaphragm, causing safety problems, while poor ion transport performance can lead to concentration polarization problems during the charge and discharge cycle, causing lithium dendrite growth. Therefore, improving the heat resistance of the diaphragm and Li + Mobility is an effective way to alleviate concentration polarization, improve cycle life and promote the development of high-performance lithium-ion batteries.

[0003] In the actual operation of LIBs, the separator must not only have thermal stability and maintain dimensional stability at high temperatures, but also have high ion transport, uniform lithium ions and inhibit dendrite growth. Poly(m-phenylene isophthalamide) (PMIA), as a new type of polymer nanofiber developed in recent years, has excellent thermal stability and is rich in polar groups such as amide, carboxyl and hydroxyl groups. It is an ideal material to replace commercial polyolefin separators. However, due to its inherent low mechanical strength, it needs to be further improved through modification. Metal-organic framework (MOF) materials have a high specific surface area and rich Lewis acid sites on their surface. In particular, the strong Zr-O bond coordination in the UIO-66 structure contributes to its stability under thermal, chemical and water conditions, which is its main advantage over other MOF materials. Zhang et al. used the traditional non-solvent phase separation process to prepare a highly safe PMIA microporous separator (Poly (m-phenyleneisophthalamide) separator for improving the heat resistance and power density of lithium-ion batteries. http: / / dx.doi.org / 10.1016 / j.jpowsour.2016.08.036). However, the mechanical properties of the prepared single PMIA separator were poor, which was not conducive to ensuring the safety of the battery during application. Hu et al. used the impregnation method to immerse the PMIA separator in an acetone solvent that dissolved MDI solid particles, and prepared PMIA-M composite separators with different immersion times. (Robustness4,4′-Diphenylmethane diisocyanate modified sponge-like porous Aramid Separators for boosting safety and electrochemical performance in lithium-ion batteries.https: / / doi.org / 10.1016 / j.jpowsour.2023.232964)However, this preparation process is relatively complicated and requires relatively more solvents, which is not suitable for large-scale industrial applications. Summary of the invention

[0004] The present invention aims at the safety problems caused by the poor thermal stability of the current polyolefin separators, as well as the complexity of existing technologies such as electrospinning and impregnation, and develops a method for preparing a composite porous separator blended with PMIA and NH2-UIO-66, namely, a non-solvent induced phase separation method. In the preparation method of the composite porous membrane, NH2-UIO-66 nanoparticles are first prepared by a simple hydrothermal synthesis method, and then blended with a slurry of PMIA, and meta-aramid PMIA is used as a supporting skeleton of a thermally stable material, and NH2-UIO-66 is used as a filler, and a sponge-like uniformly porous PMIA / NH2-UIO-66 composite separator is prepared by a non-solvent phase conversion method. The separator obtained by the present invention has both thermal stability and the performance of inhibiting the growth of lithium dendrites. The composite porous membrane is used as a lithium ion battery separator to improve the thermal stability and electrochemical performance of the battery.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing an NH2-UIO-66 modified meta-aramid lithium ion battery separator, the method comprising the following steps:

[0007] (1) adding zirconium chloride (ZrCl4) and 2-aminoterephthalic acid (NH2BDC) to N,N-dimethylformamide, and then adding acetic acid (CH3COOH) to the mixed solution, ultrasonically treating for 15-30 minutes, transferring to a stainless steel autoclave, and reacting at 110-130°C for 20-24 hours; after cooling to room temperature, washing with ethanol and centrifuging to remove the residue, and then placing in a vacuum drying oven, and drying at 140-160°C for 20-24 hours to obtain an amination NH2-UIO-66 powder;

[0008] Wherein, the mass ratio of ZrCl4 and NH2BDC is 1.0 to 1.2;

[0009] For every 50.00 ml of N,N-dimethylformamide, add 0.0600-0.0800 of ZrCl4 and 4-6 ml of CH3COOH;

[0010] (2) NH2-UIO-66 powder was dispersed in DMAC, ultrasonically treated for 15-20 min, and then added to PMIA, followed by lithium bromide (LiBr) and glycerol (Gl), mechanically stirred at room temperature for 5-6 h, and centrifuged to remove bubbles to obtain a casting solution;

[0011] The mass ratio of NH2-UIO-66 powder to meta-aramid PMIA is 0.01-0.2, and the mass ratio of glycerol to lithium bromide is 0.8-1.2; 1.0-3.0 g NH2-UIO-66 powder and 0.1-0.3 g lithium bromide are added to every 5.000 g DMAC;

[0012] (3) pouring the casting liquid onto the forming substrate, scraping it into a liquid film with a thickness of 80-120 μm, placing it into the first-stage coagulation bath, taking it out after 10-20 seconds and placing it into the second-stage coagulation bath, placing the formed PMIA / NH2-UIO-66 blended membrane into deionized water after 30-40 seconds, soaking it for 20-30 hours, then taking it out, washing it, and drying it to obtain the NH2-UIO-66 modified meta-aramid lithium ion battery separator;

[0013] The first-stage coagulation bath liquid is a mixed solution of propylene glycol and N,N-dimethylacetamide in a volume ratio of 3:6-8; the second-stage coagulation bath liquid is a mixed solution of N,N-dimethylacetyl and deionized water in a volume ratio of 3:6-8.

[0014] The prepared composite membrane is named PMIA / NH2-UIO-66, which is an asymmetric sponge-like porous membrane. The thickness of the membrane is about 30±5 μm, the liquid absorption rate is 600-650%, and the porosity is 60%-80%.

[0015] The cleaning in step (3) is performed by rinsing with deionized water and ethanol in sequence; the drying is performed by vacuum drying at 80° C. for 12 h.

[0016] Application of the NH2-UIO-66 modified meta-aramid lithium ion battery separator prepared by the method as a separator for lithium ion batteries;

[0017] The positive electrode material of the lithium-ion battery is one or more of LiCoO2, LiFePO4, and LiMn2O4, and the negative electrode material is one or more of lithium sheet, graphite, and lithium titanate;

[0018] The solute of the electrolyte is one or more of LiPF6, LiClO4, and LiAsF6 lithium salts, and the solvent is one or more of EC, PC, DMC, and DEC.

[0019] The beneficial effects of the present invention are:

[0020] (1) Benefiting from the inherent properties of PMIA, the PMIA / NH2-UIO-66 composite diaphragm prepared by the method of the present invention has excellent thermal stability and flame retardancy, thereby improving the safety performance of the battery (the diaphragm has no obvious thermal shrinkage after being treated at 200°C for 1 h).

[0021] (2) The presence of amino groups in NH2-UIO-66 enhances the wettability of the separator. The contact angle of the PMIA / NH2-UIO-66 composite separator is 18°, which is significantly lower than that of the commercial PP separator, which is 48°. At the same time, the interfacial impedance of the separator is reduced (the interfacial impedance is 99.2Ω, which is 20% lower than that of the PMIA separator) and the lithium ion migration number is increased (the lithium ion migration number is 0.79, while the lithium ion migration number of the pure PMIA separator is 0.75).

[0022] (3) The addition of NH2-UIO-66 makes Li + It is uniformly deposited during the charge and discharge process, effectively inhibiting the growth of lithium dendrites, and exhibiting long-life electrochemical stability, improving the cycle performance and rate performance (after 200 cycles at 0.2C, the battery's discharge capacity remains at 137.2mAh / g, while the battery assembled with pure PMIA diaphragm has a discharge capacity of only 121.37mAh / g after 200 cycles at 0.2C).

[0023] (4) The addition of NH2-UIO-66 nanoparticles improves the mechanical strength of the pure PMIA separator. The tensile strength of the PMIA / NH2-UIO-66 composite separator is 22.37 MPa, which is 1.34 times the tensile strength of the pure PMIA separator (16.63), ensuring the safety of the battery under conditions such as squeezing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The SEM images of the NH2-UIO-66 nanoparticles and PMIA / NH2-UIO-66 composite membrane prepared in Example 1 are shown in FIG. Figure 1 a is the surface morphology of NH2-UIO-66 nanoparticles. Figure 1 b is the top surface morphology of PMIA / NH2-UIO-66 composite membrane. Figure 1 c is the bottom surface morphology of the PMIA / NH2-UIO-66 composite membrane.

[0025] Figure 2 This is a diagram showing the dimensional changes of the pure PMIA membrane and the PMIA / NH2-UIO-66 composite membrane prepared in Example 2 before and after heat treatment.

[0026] Figure 3 This is the interface impedance diagram corresponding to the button battery assembled with the pure PMIA membrane and the PMIA / NH2-UIO-66 composite membrane prepared in Example 3.

[0027] Figure 4Nyquist impedance spectra (inset), polarization curves and Li / / Separator / / Li cells assembled with pure PMIA separator and PMIA / NH2-UIO-66 composite separator prepared in Example 1 + Migration number diagram; where Figure 4 a is the Nyquist impedance spectrum (inset), polarization curve and Li + Migration number map, Figure 4 b Nyquist impedance spectrum (inset), polarization curve and Li + Migration number graph.

[0028] Figure 5 This is a comparison chart of the mechanical properties of the pure PMIA membrane and the PMIA / NH2-UIO-66 composite membrane prepared in Example 2.

[0029] Figure 6 This is a test diagram of the cycle performance of a lithium-ion battery assembled with the PMIA membrane and PMIA / NH2-UIO-66 composite membrane prepared in Example 3. DETAILED DESCRIPTION

[0031] The positive electrode material used in the following embodiments of the present invention is LiFePO4.

[0032] The PMIA / NH2-UIO-66 composite membrane prepared in the following examples is an asymmetric sponge-like porous membrane with a thickness of 30±5μm, a liquid absorption rate of 600-650%, and a porosity of 60%-80%. The preparation adopts a non-solvent phase inversion method, and the PMIA / NH2-UIO-66 casting liquid is placed in the first-stage coagulation bath DMAc / Gl (v:v=7:3) for 15s, then taken out and immediately placed in the second-stage coagulation bath DMAc / H2O (v:v=3:7) for 35s, then taken out and washed several times. But it is not limited to this.

[0033] Example 1

[0034] 1) Synthesis of NH2-UIO-66 powder by hydrothermal method

[0035] 74.52 mg of ZrCl4 and 73.21 mg of NH2BDC were added to a beaker containing 50.00 ml of DMF, and then 5.00 ml of CH3COOH was added to the mixed solution. After ultrasonic treatment for 30 min, it was transferred to a 100 ml stainless steel autoclave and heated in an oven at 120 ° C for 24 h. After cooling to room temperature, it was washed with ethanol and centrifuged to remove the residue, and then placed in a vacuum drying oven and dried at 150 ° C for 24 h to obtain NH2-UIO-66 powder.

[0036] 2) Preparation of casting solution for blended membrane

[0037] 2.000g of NH2-UIO-66 powder obtained in step 1) was dispersed in 5.000g of DMAC, and after ultrasonic treatment for 15min, the solution was added to 30.000g of meta-aramid PMIA, and then 1% (mass percentage of PMIA) of porogens lithium bromide and glycerol were added. After mechanical stirring at room temperature for 5h, the bubbles were removed by centrifugation, and finally a mixed casting solution of PMIA / NH2-UIO-66 was obtained.

[0038] 3) Prepare the first and second coagulation baths

[0039] A mixed solution of glycerol and N,N-dimethylacetamide in a volume ratio of 3:7 is prepared as a first-stage coagulation bath; and a mixed solution of N,N-dimethylacetamide and deionized water in a volume ratio of 3:7 is prepared as a second-stage coagulation bath.

[0040] 4) Preparation of blend membranes by phase separation method

[0041] The casting liquid prepared in step 2) is poured onto the molding substrate, the scraper thickness is adjusted to 80 μm, and a liquid film is scraped using an automatic scraper. The film is slowly and evenly placed in the first-stage coagulation bath. After 15 seconds, it is taken out and placed in the second-stage coagulation bath. After 35 seconds, the formed PMIA / NH2-UIO-66 blend membrane is taken out from the coagulation bath and placed in deionized water. It is soaked for 24 hours to remove residual solvents and additives. After that, it is taken out and rinsed repeatedly with deionized water and ethanol for 3 times. It is placed in a vacuum oven and dried at 80°C for 12 hours to obtain a PMIA / NH2-UIO-66 composite diaphragm.

[0042] The contact angle analyzer (KRUSSDSA255, Germany) was used to test the wettability of the electrolyte of the diaphragm. The diaphragm was cut into strips of approximately 10 mm × 20 mm and pasted to the edge of a glass slide. The electrolyte was dripped onto the surface of the diaphragm using a microinjector. 4-5 points were measured for each sample and the average value was taken. By quickly dripping 20 μL of electrolyte solution onto the membrane surface, the wetting behavior of the electrolyte was observed. Finally, the contact angle of the PMIA / NH2-UIO-66 composite diaphragm was 18°, indicating good wettability. At the same time, the battery was assembled into a lithium / diaphragm / lithium electrode system and tested on an electrochemical workstation (PARSTAT 2273, AMETEK, USA). The interfacial impedance and polarization curves before and after polarization were tested using the AC impedance method and the timed amperometric method. The test conditions were: the voltage was set to 10 mV and the time was set to 1000 s. The results show that the interfacial impedance of the PMIA / NH2-UIO-66 composite membrane is 99.2Ω, which is 20% lower than that of the PMIA membrane, and the lithium ion migration number is 0.79, while the lithium ion migration number of the pure PMIA membrane is 0.75.

[0043] Example 2

[0044] 1) The hydrothermal method for synthesizing NH2-UIO-66 powder is the same as step 1) in Example 1;

[0045] 2) The casting solution for preparing the blended membrane is the same as step 2) of Example 1;

[0046] 3) preparing the first and second coagulation baths in the same manner as step 3) of Example 1;

[0047] 4) Preparation of blended film

[0048] The casting liquid prepared in step 1) is poured onto the molding substrate, the scraper thickness is adjusted to 100 μm, and a liquid film is scraped by an automatic scraper, and then slowly and evenly placed in the first-stage coagulation bath. After 15 seconds, it is taken out and placed in the second-stage coagulation bath. After 35 seconds, the formed PMIA / NH2-UIO-66 blend membrane is taken out from the coagulation bath and placed in deionized water, soaked for 24 hours to remove residual solvents and additives, then taken out and rinsed repeatedly with deionized water and ethanol for 3 times, and placed in a vacuum oven and dried at 80°C for 12 hours to obtain a PMIA / NH2-UIO-66 composite diaphragm.

[0049] The diaphragm was cut into discs with a diameter of 19 mm, and heated to 50°C, 100°C, 150°C, and 200°C respectively and kept for 1 hour to observe its thermal stability and calculate its thermal shrinkage. Finally, it was found that the diaphragm had almost no dimensional changes at different temperatures, indicating good thermal stability. At the same time, using a universal tensile machine, the test samples were cut into 6.0cm×1.0cm strips, and the tensile strength and elongation at break of the membrane material were tested at a speed of 5.0mm / min. The tensile strength of the composite diaphragm is 22.37MPa, which is 1.34 times the tensile strength of the pure PMIA diaphragm (16.63).

[0050] Example 3

[0051] 1) The hydrothermal method for synthesizing NH2-UIO-66 powder is the same as step 1) in Example 1;

[0052] 2) The casting solution for preparing the blended membrane is the same as step 2) of Example 1;

[0053] 3) preparing the first and second coagulation baths in the same manner as step 3) of Example 1;

[0054] 4) Preparation of blended film

[0055] The casting liquid prepared in step 1) is poured onto the molding substrate, the scraper thickness is adjusted to 120 μm, and a liquid film is scraped by an automatic scraper, and then slowly and evenly placed in the first-stage coagulation bath. After 15 seconds, it is taken out and placed in the second-stage coagulation bath. After 35 seconds, the formed PMIA / NH2-UIO-66 blend membrane is taken out from the coagulation bath and placed in deionized water. It is soaked for 24 hours to remove residual solvents and additives. After that, it is taken out and rinsed repeatedly with deionized water and ethanol for 3 times, and then placed in a vacuum oven and dried at 80°C for 12 hours to obtain a PMIA / NH2-UIO-66 composite diaphragm.

[0056] After drying, the PMIA / NH2-UIO-66 composite diaphragm was pressed into 19mm discs with a punching machine and assembled into CR2032 button batteries (LiFePO4 was selected as the positive electrode, lithium sheet was selected as the negative electrode, and the electrolyte was 1M LiPF6 ternary carbonate solution). The constant current charge and discharge cycle and rate performance of the lithium battery were tested using the LAND system; the stainless steel sheet / diaphragm / stainless steel sheet was assembled and the EIS impedance test was performed using an electrochemical workstation model PARSTAT 2273. The experimental results show that the ion conductivity of the battery assembled with the PMIA diaphragm is 0.79mS / cm. After 200 cycles of charge and discharge, the discharge specific capacity is 137.2mAh / g, and the capacity retention rate is 92.2%, which is better than the same type of battery assembled with the PMIA membrane, such as Figure 6 shown.

[0057] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0058] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing an NH2-UIO-66 modified meta-aramid lithium ion battery separator, characterized in that the method comprises the following steps: (1) adding zirconium chloride (ZrCl4) and 2-aminoterephthalic acid (NH2BDC) to N,N-dimethylformamide, and then adding acetic acid (CH3COOH) to the mixed solution, ultrasonically treating for 15-30 minutes, transferring to a stainless steel autoclave, and reacting at 110-130°C for 20-24 hours; after cooling to room temperature, washing with ethanol and centrifuging to remove the residue, and then placing in a vacuum drying oven, and drying at 140-160°C for 20-24 hours to obtain an amination NH2-UIO-66 powder; in, The mass ratio of ZrCl4 and NH2BDC is 1.0 to 1.2; For every 50.00 ml of N,N-dimethylformamide, add 0.0600-0.0800 of ZrCl4 and 4-6 ml of CH3COOH; (2) NH2-UIO-66 powder was dispersed in DMAC, ultrasonically treated for 15-20 min, and then added to PMIA, followed by lithium bromide (LiBr) and glycerol (Gl), mechanically stirred at room temperature for 5-6 h, and centrifuged to remove bubbles to obtain a casting solution; The mass ratio of NH2-UIO-66 powder to meta-aramid PMIA is 0.01-0.2, and the mass ratio of glycerol to lithium bromide is 0.8-1.2; 1.0-3.0 g NH2-UIO-66 powder and 0.1-0.3 g lithium bromide are added to every 5.000 g DMAC; (3) pouring the casting liquid onto the forming substrate, scraping it into a liquid film with a thickness of 80-120 μm, placing it into the first-stage coagulation bath, taking it out after 10-20 seconds and placing it into the second-stage coagulation bath, placing the formed PMIA / NH2-UIO-66 blended membrane into deionized water after 30-40 seconds, soaking it for 20-30 hours, then taking it out, washing it, and drying it to obtain the NH2-UIO-66 modified meta-aramid lithium ion battery separator; The first-stage coagulation bath liquid is a mixed solution of propylene glycol and N,N-dimethylacetamide in a volume ratio of 3:6-8; the second-stage coagulation bath liquid is a mixed solution of N,N-dimethylacetyl and deionized water in a volume ratio of 3:6-8.

2. The method for preparing the NH2-UIO-66 modified meta-aramid lithium ion battery separator as described in claim 1, characterized in that the obtained separator is an asymmetric sponge-like porous membrane, and the thickness of the separator is about 30±5μm, the liquid absorption rate is 600-650%, and the porosity is 60%-80%.

3. The method for preparing the NH2-UIO-66 modified meta-aramid lithium ion battery separator according to claim 1, characterized in that The cleaning in step (3) is to rinse with deionized water and ethanol repeatedly in sequence; the drying is to dry in vacuum at 80° C. for 12 hours.

4. Application of the NH2-UIO-66 modified meta-aramid lithium ion battery separator prepared by the method according to claim 1, characterized in that it is used as a separator for lithium ion batteries; The positive electrode material of the lithium-ion battery is one or more of LiCoO2, LiFePO4, and LiMn2O4, and the negative electrode material is one or more of lithium sheet, graphite, and lithium titanate; The solute of the electrolyte is one or more of LiPF6, LiClO4, and LiAsF6 lithium salts, and the solvent is one or more of EC, PC, DMC, and DEC.

Citation Information

Cited By

  • Polyisophthaloyl metaphenylene diamine-based electrostatic spinning flame-retardant diaphragm and application thereof

    CN120061055A